(untitled) (Journal of Philosophy Culture and Political Science, 2026)
This article examines the problem of intonation within the philosophy of language, interpreted not as an exclusively phonetic phenomenon but as a fundamental dimension of meaning. Specifically, this work provides philosophical view regarding to Kazakh intonation having been characterized in own book “Ädebiet tanytqysh” by Kazakh scholar and enlightener Akhmet Baitursynuly. In studying Kazakh speech prosody Baitursynuly conceptualized such categories as yrğaq, jorğaq, shumaq, tarmaq, bunaq, and aishyq, and thereby proposed an integral rhythmic-intonational model of language. This study argues that intonation defined by Kazakh scholar is essential for shaping utterances and for conveying illocutionary force within kazakh communicative interaction. By situating this issue within central debates in the philosophy of language - such as the distinction between propositional content and illocutionary force, the interplay between semantics and pragmatics, and the problem of contextual underdetermination – this study shows that intonation contributes to shaping the semantic structure of an utterance. Baitursynuly’s intonological framework is understood as a philosophically meaningful effort to account for how meaning is realized in Kazakh live speech. A philosophical examination of this theoretical model enables a more coherent understanding of Kazakh speech intonational structure and its role in the formation of meaning, thought, and Kazakh consciousness. In a broader cultural and conceptual context, such a view strengthens scholars’ interest to Kazakh language considered as a cornerstone of national and cultural identity. Kazakh intonation is viewed as a medium through which meaning gains modal, pragmatic, and expressive dimensions, connecting kazakh linguistic form with speech acts. In conclusion, Kazakh prosody constitutes a structural prerequisite for the realization of Kazakh meaning and contributes to its ontological actualization in speech. Keywords: intonation, A. Baitursynuly’s language philosophy, Kazakh intonation, rhythm, implicative and explicative world, resonance.